Perceived Effects of Embedding a Learning Strategy Course in a Year 8 Science Program - McGlynn, Penelope Jane (Curtin University, 2003)
A year long learning strategy course was designed and embedded in a Year 8 science curriculum. The Science Learning Strategy (SLS) program aimed to improve student ability to apply learning strategies to science, increase student achievement in science and to augment students' feelings of control over their science learning, so that their perceived competence was maximised. Achievement of these aims was monitored by collecting perceptions from students, parents and the teacher/researcher via a range of devices including questionnaires, work samples and interviews. The program overall was regarded as successfully achieving all three aims by 22 of the 24 students. The other two students found that only some aspects of the course were helpful, and felt they had learned little from the program. Thirty three percent of parents attributed positive changes in their daughter's study and learning strategies to participation in the SLS program (the remainder were unsure, or did not know of any changes). In relation to perception of academic performance, 38% of the parents interviewed believed that the SLS had a positive effect on their daughter's achievement in science. Several of these parents reported very positive effects on performance. The remainder were not sure or did not know if there had been any positive effects. No parents mentioned that the SLS program had caused a drop in science performance. The proportion of parents believing their daughters blamed disappointing results on factors they couldn't control dropped from 45% at the start of the year, to 22% by the end of the SLS program. After the intervention, 33% of parents reported that their daughters had come to believe that their science performance was affected by many factors, most of which they could control.The teacher/researcher observed strong improvement in student ability to apply learning strategies to science as a result of participation in the program. Students were also observed by the teacher/researcher, to have been assisted by the intervention to realise that their science performance was governed not only by their natural ability, but also by factors such as studying behaviour and affective influences. In particular, the program appeared to the teacher/researcher to have helped students realise that they had control over their use of learning strategies, and that this control could influence their science performance. However, the teacher/researcher found that no statistically significant changes in science achievement resulted from student participation in the SLS course. The other objective of the research was to investigate the extent to which learning strategy education was valued and implemented by Western Australian science teachers. The 218 returned surveys revealed that most respondents recognised the need to teach these skills during science lessons. Seventy six percent of respondents considered the delivery of learning strategy instruction in the lower school science classroom to be as important, or more important, than teaching subject processes and content. Sixty seven percent recognised that improving study strategies can improve confidence and/or motivation.Many teachers, however, had not been able to convert these views into consistent classroom practice. A moderate proportion of teachers reported teaching a variety of learning strategies; 74% of the respondents agreed that learning strategy instruction could improve performance in science. Only one teacher specifically mentioned incorporating the teaching of learning strategies with instruction in science process and content. As a future outcome of this project, the teacher/researcher will encourage other teachers to embed learning strategy instruction within the science curriculum, so that their students come to feel more in control of their learning and can learn more effectively.